Rare variants in TMEM132D in a case-control sample for panic disorder - Quast, Carina; Altmann, Andre; Weber, Peter; Arloth, Janine; Bader, Daniel; Heck, Angela; Pfister, Hildegard; Müller-Myhsok, Bertram; Erhardt, Angelika; Binder, Elisabeth B. (American journal of medical genetics. Part B, Neuropsychiatric genetics, 2012)
Genome‐wide association studies have identified common variants associated with common diseases. Most variants, however, explain only a small proportion of the estimated heritability, suggesting that rare variants might contribute to a larger extent to common diseases than assumed to date. Here, we use next‐generation sequencing to test whether such variants contribute to the risk for anxiety disorders by re‐sequencing 40 kb including all exons of the TMEM132D locus which we have previously shown to be associated with panic disorder and anxiety severity measures. DNA from 300 patients suffering from anxiety disorders, mostly panic disorder (84.7%), and 300 healthy controls was screened for the presence of genetic variants using next‐generation re‐sequencing in a pooled approach. Results were verified by individual re‐genotyping. We identified 371 variants of which 247 had not been reported before, including 15 novel non‐synonymous variants. The majority, 76% of these variants had a minor allele frequency less than 5%. While we did not identify additional common variants in TMEM132D associated with panic disorders, we observed an overrepresentation of presumably functional coding variants in healthy controls as compared to cases as well as a higher rate of private coding variants in cases, with one non‐synonymous coding variant present in four patients but not in any of the matched controls nor in over 5,500 individuals of different ethnic origins from publicly available re‐sequencing datasets. Our data suggest that not only common but also putatively functional and/or rare variants within TMEM132D might contribute to the risk to develop anxiety disorders. © 2012 Wiley Periodicals, Inc.